Isolation and Flow Cytometry Characterization of Extracellular‐Vesicle Subpopulations Derived from Human Mesenchymal Stromal Cells. (9th January 2019) - Gorgun, Cansu; Reverberi, Daniele; Rotta, Gianluca; Villa, Federico; Quarto, Rodolfo; Tasso, Roberta
Abstract: This unit describes protocols for isolating subpopulations of extracellular vesicles (EVs) purified from human adipose tissue–derived mesenchymal stromal cells by density gradient centrifugation and for characterizing them by flow cytometry (FCM). Determining the optimal strategy for isolating EVs is a critical step toward retrieving the maximal amount while ensuring the recovery of different vesicular subtypes. The first protocol details density gradient centrifugation to isolate both exosomes and microvesicles. In the second protocol, characterization of EV subpopulations by FCM is depicted, taking advantage of non‐conventional modalities, in accordance with the latest technical indications. The procedures described here can be easily reproduced and can be employed regardless of the cell type used to obtain EVs. © 2019 by John Wiley & Sons, Inc.